SIFAT- SIFAT GEL GELATIN TULANG CAKAR AYAM - D. A. P. Puspitasari -; V. P. Bintoro -; B. E. Setiani - (Universitas Muhammadiyah Semarang, 2013)
The purpose of the study was to investigate the soaking effect of different HCl concentration, soaking time and the interaction on geling properties (pH values, yield, viscocity, gel strength, melt time and gel of temperature and time) of chicken shank bone gelatin. The materials used were chicken shank bones, HCl, NaOH and liquid soda. The research design used was completely randomized design (CRD) factorial, in which factor A was the concentration of HCl (a1 = HCl 2%, a2 = HCl 3,5% and a3 = HCl 5%) and factor B was soaking time (b1 = 24 hours, b2 = 36 hours and b3 = 48 hours). The result showed that the use of different HCl concentration, soaking time and the interaction affected geling properties (pH values, yield, viscocity, gel strength, melt time and gel of temperature and time) of chicken shank bone gelatin. The best result came from the interaction of soaking chicken shank bone in 5% concentration of HCl for 48 hours at 4 pH value, yield 1,31%, viscocity (40 – 60 OC) 1,62 – 3,03 cP, gel strength 228,81 bloom, melt in 40 – 60 OC for 0,58 – 3,29 minutes, gel in 10,7 OC for 7,5 minutes. In conclusion, according to GMIA (2012), gel properties of chicken shank bones gelatin by soaking in 5% concentration of HCl for 48 hours recommended to become alternative food additive in food industry.